RISK ASSESSMENT K3 PADA PROSES PENGOPERASIAN SCAFFOLDING PADA PROYEK APARTEMEN PT. X DI SURABAYA - Persada, Yudha Bagus (The Indonesian Journal of Occupational Safety and Health, 2015)
ABSTRACTProblems that arised when employees works at height are worker did not wear full body harness, lanyard did not hanged perfectly to handrail, did not works according to the procedure, and using unsafe scaffolding. Hazard identification and risk assessment used as prevention for accident when operating scaffolding. This study was an observational study with cross sectional design and analyzed descriptively. The design used for the study carried out by observing cause and effect within a period of time and space. Objects of this study were frame scaffolding and scaffolding PCH, while subjects of this study were SHE Officer, SHE supervisor, workers section structure, finishing, plumbing hydrant, and mechanical engineering. Results of hazard identification using JSA method founds 43 potential hazards originating from 4 different types of work in this project. The results of the risk assessment of 43 potential hazards have been found that 1 hazard have low risk, 40 hazards have moderate risk , and high risk hazard are 2. The dominant risk from the operation of the scaffolding was 40 potential hazards or 93% of the total potential hazards and high-risk hazard eventhough only 5% of all potential hazards remains a top priority and should be controlled soon to reduce the high and medium risk becomes low risk. The likelihood-based control is more possible to reduce risk level than severity-based control.Keywords: risk assessment, scaffolding operation